52nd AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics and Materials Conference 2011
DOI: 10.2514/6.2011-1917
|View full text |Cite
|
Sign up to set email alerts
|

An Intrinsic Description of the Nonlinear Aeroelasticity of Very Flexible Wings

Abstract: A modal solution is presented to the aeroelastic equations of very flexible wings in intrinsic form, that is written using inertial velocities and strains as primary variables. After assuming 2-D thin-airfoil aerodynamics on the wing sections, it is shown that the equations of motion can be written in canonical state-space form on the intrinsic modal coordinates without any matrix inversion and including only quadratic nonlinearities. Flutter characteristics are readily obtained from a linearized description o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…Moreover, Patil et al developed a non-linear 1D formulation for laminated box beams by adopting an asymptotic technique to compute the cross-sectional mechanical properties [13,14]. Later, Palacios et al used the same formulation to evaluate the aeroelastic behavior of highly flexible wings [15]. Nowadays, the rapid increase of the computational power has motivated the development in the area of computational fluid dynamics (CFD).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Patil et al developed a non-linear 1D formulation for laminated box beams by adopting an asymptotic technique to compute the cross-sectional mechanical properties [13,14]. Later, Palacios et al used the same formulation to evaluate the aeroelastic behavior of highly flexible wings [15]. Nowadays, the rapid increase of the computational power has motivated the development in the area of computational fluid dynamics (CFD).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting model will then be tightly coupled with unsteady aerodynamics obtained from thin-strip approximations, as it was done by Palacios and Epureanu. 13 More complex aerodynamics based on the linearized unsteady vortex-lattice formulation of Murua et al, 7 which accounts for large-deformations in the equilibrium conditions, could be considered, but a 2-D description was selected for simplicity in a first demonstration of the approach. This will provide a compact description of the problem suitable for both modelling and control design.…”
Section: Introductionmentioning
confidence: 99%
“…The current study uses 11 bending modes and 1 axial mode which produced results that match well with previous studies using 2D aerodynamic approximations (see Table 3), whereas 3D aerodynamic methods such as UVLM more accurately reflect tip effect which have a noticeable impact on the computed flutter speed. 18 Time-domain simulation shows that structural nonlinearities do not give rise to any limit-cycle oscillations on the Goland wing at post-flutter speeds. Patil et al 26 also confirmed that structural nonlinearities in themselves are unable to create limit-cycle oscillations post-flutter.…”
Section: B Aeroelastic Model Verificationmentioning
confidence: 99%
“…The exact form of the aerodynamic forces in the modal description, derived using Wagner's function, is described by Palacios and Epureanu. 18 These forces can be approximated by a quadratic coupling between the velocity modes augmenting the modal ODE. The aeroelastic modal dynamics can then be written as:…”
Section: Aeroelastic Formulationmentioning
confidence: 99%
See 1 more Smart Citation